PENGARUH LINGKUNGAN KELUARGA DAN MINAT BELAJAR TERHADAP HASIL BELAJAR PAI MELALUI MOTIVASI BELAJAR SEBAGAI VARIABEL INTERVENING - Rusmayani, Rusmayani; Jumari, Jumari; Khasanah, Uswatun; Faizah, Kurniyatul (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
The lack of family support, interest, and motivation impacts students' low learning outcomes. This study aims to examine and analyze the direct and indirect effects of family environment, interest, and learning motivation on learning outcomes. This research uses an ex post facto quantitative method with SEM-PLS analysis; data were collected using questionnaires and learning outcome documents. The results show: 1) Family environment has a direct, positive, and significant effect on learning interest; 2) Learning interest has a direct, positive, and significant effect on learning motivation; 3) Learning motivation does not have a direct and significant effect on learning outcomes; 4) Family environment does not have a direct and significant effect on learning motivation; 5) Family environment has a direct, positive, and significant effect on learning outcomes; 6) Learning interest does not have a direct, positive, and significant effect on learning outcomes; 7) Indirectly, family environment does not have a significant effect on learning outcomes through learning motivation; 8) Indirectly, learning interest does not have a significant effect on learning outcomes through learning motivation; 9) Indirectly, family environment has a positive and significant effect on learning motivation through learning interest; 10) Indirectly, family environment does not have a positive and significant effect on learning outcomes through learning interest.